Antifungal susceptibility patterns among candida species isolated from blood at Universiti Kebangsaan Malaysia Medical Centre - Siti Umairah Hamid,; Sharon Tan,; Siti Nurwani Ahmad Ridzuan,; Mohd Syazwan Che Seman,; Ramliza Ramli,; Tzar Mohd Nizam Khaithir, (Universiti Kebangsaan Malaysia, 2012)
Many challenges arise in candidaemia treatment which involves emergence of antifungal resistance. New species have been identified due to improved methods of detection and some are resistant to commonly prescribed antifungal agents such as fluconazole and amphotericin B. Therefore, the objective of the study was to observe any changes in the susceptibility patterns and distribution of Candida species. This cross sectional study was conducted at the Department of Medical Microbiology and Immunology in UKMMC, a tertiary teaching hospital. One hundred and fifty one data were collected from the department’s laboratory records from January 2008 to December 2010. The yeasts were identified using ID32C carbohydrate assimilation tests whilst the antifungal susceptibility test was performed using Sensititre® YeastOne® broth microdilution method. Antifungal agents tested included amphotericin B, fluconazole, itraconazole, voriconazole, 5-flucytosine and caspofungin. Out of 151 blood isolates, 47 (31.1%) were Candida albicans and 104 (68.9%) were non-albicans Candida species. Candida tropicalis has surpassed C. albicans as the most commonly isolated Candida species from blood. Overall susceptibility (as compared to 2005-2006 data in brackets) to caspofungin was 99.3% (n/a), 5-flucytosine 97.4% (98%), amphotericin B 94.7% (100%), voriconazole 92.7% (98%), fluconazole 86.8% (90%) and itraconazole 39.1% (40%). In conclusion, although the isolates were generally still susceptible to amphotericin B and fluconazole, resistance to these drugs is increasing.